Association of out of hospital paediatric early warning score with need for hospital admission in a Scottish emergency ambulance population. (December 2020) - Corfield, Alasdair R.; Booth, Katherine L.; Clerihew, Linda; Staines, Harry; Stewart, Elaine; Rooney, Kevin D.
Abstract : Objective: Physiological derangement, as measured by paediatric early warning score (PEWS) is used to identify children with critical illness at an early point to identify and intervene in children at risk. PEWS has shown some utility as a track and trigger system in hospital and also as a predictor of adverse outcome both in and out of hospital. This study examines the relationship between prehospital observations, aggregated into an eight-point PEWS (Scotland), and hospital admission. Methods: A retrospective analysis of all patients aged less than 16 transported to hospital by the Scottish Ambulance Service between 2011 and 2015. Data were matched to outcome data regarding hospital admission or discharge and length of stay. Results: Full data were available for 21 202 paediatric patients, of whom 6340 (29.9%) were admitted to hospital. Prehospital PEWS Scotland was associated with an odds ratio for admission of 1.189 [95% confidence interval (CI): 1.176–1.202; P  < 0.001]. The area under receiver operating curve of 0.617 (95% CI: 0.608–0.625; P  < 0.001) suggests poorly predictive ability for hospital admission. There was no association between prehospital PEWS Scotland and length of hospital stay. Conclusion: These data show that a single prehospital PEWS Scotland was a poor predictor of hospital admission for unselected patients in a prehospital population. The decision to admit a child to hospital is not solely based on the physiological derangement of vital signs, and hence physiological-based scoring systems such as PEWS Scotland cannot be used as the sole criteria for hospital admission, from an undifferentiated prehospital population.